Observations of Hall reconnection physics far downstream of the X-line - Mistry,R; Eastwood,JP; Haggerty,CC; Shay,MA; Phan,TD; Hietala,H; Cassak,PA (Physical Review Letters, 2016)
Observations made using the Wind spacecraft of Hall magnetic fields in solar wind reconnection exhausts are presented. These observations are consistent with the generation of Hall fields by a narrow ion inertial scale current layer near the separatrix, which is confirmed with an appropriately scaled particle-in-cell simulation that shows excellent agreement with observations. The Hall fields are observed thousands of ion inertial lengths downstream from the reconnection X line, indicating that narrow regions of kinetic dynamics can persist extremely far downstream.